(3GdTQM GdUZjQ Ydi efjI GdeUdjs - (3GdMdHj, EHQGgje Hf eMeO Hf EHQGgje, J (B956(3g`s ((3eMeO GHf OQhjTs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdYHGOI eaJJM GdSYGOI(B... (3hHYO ajbhd GdeaJbQ(B... (3bO cfJ TQMJ cJGH efjI GdeUdj TQMG hSejJg(B: (3HZjI GdeJedj dcf QCjJ ajg HYV GdEWGdI(B... (3aCMHHJ Cf CNJUQ(B...s
(3BNQgG (B:s
(3hdh de jcf bGOQG Ydi egQgG hdCf jdbi Gddg hegQgG aj PeJg NjQ dg ef Cf jWF GeQCJg dG JUdj bGd Gddg JYGdi(B: (3hCeQ Cgdc HGdUdGI(B... (3hfSCd Gddg JYGdi MSf GdYGajI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B66s
(3cTa GdXfhf(B: (3L(B2(3, U(B1886s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis